Profesionalisme Nazhir dalam Pengelolaan Wakaf Uang: Belajar dari Tata Kelola Wakaf Uang di Bangladesh - Ma'ruf Sya'ban; Arin Setiyowati (BALANCE: Economic, Business, Management and Accounting Journal, 2019)
ABSTRACT This study aims to carry out a focused investigation on the implementation of Nazhir's professionalism in productively and contextually using cash waqf according to the needs of the ummah. Both for religious, social and economic programs, whose origin is for the benefit of the people through Islamic Financial Institutions, in this case Islamic Banks. Research conducted in literature on waqf management in Bangladesh found that the prototype profile and Nazhir's professional role had a significant impact in the efforts to utilize cash waqf (cash waqf) for the welfare of the people. Keywords                    : Good Nazhir Governance, Nazhir, Wakaf Tunai (Cash Waqf)Correspondence to        : maruf@um-surabaya.ac.id ABSTRAK Penelitian ini bertujuan untuk melakukan penyelidikan terfokus pada implementasi profesionalisme Nazhir dalam mendayagunakan wakaf uang secara produktif dan kontekstual dengan kebutuhan umat. Baik untuk program keagamaan, sosial dan ekonomi yang muaranya adalah untuk kemashlahatan umat melalui Lembaga Keuangan Syariah, dalam hal ini Bank Syariah. Penelitian yang dilakukan secara kepustakaan pada tata Kelola wakaf di Bangladesh ini menemukan terkait prototype profil dan peran Nazhir secara profesional memiliki dampak yang signifikan dalam upaya pendayagunaan wakaf tunai (Cash Waqf) untuk kesejahteraan umat. Kata Kunci                  : Good Nazhir Governance, Nazhir, Wakaf Tunai (Cash Waqf)